Respuesta :
Hey there!
To start, first simplify your expression by distributing your values to the equation inside the parenthesis:
5(-3x - 2) - (x - 3) = -4(4x + 5) + 13
(5*-3x)+(5*-2)-x-3=(-4+4x)+(-4*5)+13
-15x-10-x-3=-16x-20+13
Now, combine your like terms, or terms that are raised to the same power and have the same variables that are also raised to the same power:
-15x-10-x-3=-16x-20+13
(-15x-x)+(-10-3)=-16x+(-20+13)
-16x-7=-16x-7
Because your equation is set equal to itself, your answer would be all real solutions as any real number can be plugged into the variable and have a valid answer.
Hope this helps and have a wonderful day! :)
To start, first simplify your expression by distributing your values to the equation inside the parenthesis:
5(-3x - 2) - (x - 3) = -4(4x + 5) + 13
(5*-3x)+(5*-2)-x-3=(-4+4x)+(-4*5)+13
-15x-10-x-3=-16x-20+13
Now, combine your like terms, or terms that are raised to the same power and have the same variables that are also raised to the same power:
-15x-10-x-3=-16x-20+13
(-15x-x)+(-10-3)=-16x+(-20+13)
-16x-7=-16x-7
Because your equation is set equal to itself, your answer would be all real solutions as any real number can be plugged into the variable and have a valid answer.
Hope this helps and have a wonderful day! :)
first we should simplify!
to do this you need to use the distributive property
-15x - 10 - x + 3 = -16x -20 + 13
now add like terms
-16x - 7 = -16x -7
this is true
S = {Reals}
^
|
|
S means set
{reals} means all real numbers
i hope this helps !!
to do this you need to use the distributive property
-15x - 10 - x + 3 = -16x -20 + 13
now add like terms
-16x - 7 = -16x -7
this is true
S = {Reals}
^
|
|
S means set
{reals} means all real numbers
i hope this helps !!